Structural and Optical Properties of CdS:20%In Films Prepared by Thermal Co-Evaporation method (Baghdad Science Journal, 2025)
The CdS;In films of Thickness 7500Ao at( 20% In) concentration have been Prepared by double evaporation method in Vacuum on glass substrate at 100co .Optical and structural Properties have been studied. It has been found that all the films are Polycrystalline with high peak. The Doping the film lead to increase in absorption coefficient, extinction coefficient and imaginary dielectric constant and decreasing the energy of band gap, reflectance, reflective index and real dielectric constant.